Two new species of Enoplolaiminae (Enoplida: Thoracostomopsidae) from Río Negro and Chubut, Argentina - Pastor, Catalina; Russo, Virginia Lo (Zootaxa, 2021)
Two new species of free-living marine nematodes of the subfamily Enoplolaiminae are described from Río Negro and Chubut Provinces, Argentina. Enoplolaimus variispiculum sp. n. is characterized by having asymmetric spicules, different in size and distal tips. It is the only species with this characteristic in the whole genus. Mesacanthoides flagellatum sp. n. is characterized by mandibles texture, weakly cuticularized and mottled and mandibular plates with pronounced “v” shaped incision posterior to the anterior bar. Cephalic capsule wider than long with setae on posterior end, males with long spicules, complex gubernaculum and flagellate tail.